Urgensi Pembaruan Hukum Jaminan Fidusia terhadap Kendaraan Bermotor Listrik di Indonesia - Adinda Dwi Larasati (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2026)
The purpose of this study is to analyze the legal regulations governing fiduciary liens in Indonesia and the urgency of updating the law on fiduciary liens as they relate to battery electric vehicles. This study employs a normative legal research method using a legislative approach and a conceptual approach. The results of the study indicate that the legal regulations governing fiduciary security in Indonesia are currently based on Law Number 42 of 1999, which provides legal certainty regarding preferential rights for creditors, the obligation to register fiduciary security, and the mechanisms for the enforcement of the collateral. Updates to fiduciary security laws are necessary to accommodate the economic characteristics of battery electric vehicles as collateral, particularly regarding the valuation mechanism of the collateral, provisions for mitigating the risk of depreciation of electric vehicles, and certainty in enforcement procedures to provide legal protection for the parties involved.